Proposta de soluções em estrutura pré-fabricada como alternativa para o projeto de uma escola em concreto armado convencional (moldado in loco) - Farenzena, Andréia (2014)
The purpose of this research is to show the precast concrete framing as an alternative for the structural design of a standardized school project, which is a public building to be constructed in more than one city, actually using sitecast concrete framing. Therefore, two kinds of precast framing systems were selected as probable solutions: unidirectional precast slabs and hollow core prestressed concrete slabs. Thus, the structural design for both proposals was elaborated, consisting of beams, columns, corbels and sockets details. Based in the structural designs that were previously developed, a comparative analysis between the characteristics of the systems was performed. As a result, it was possible to reduce the number of structural elements in both kinds of precast framing systems. Also, the consumption of concrete and steel were estimated, and was verified that, in general, precast concrete structures consume greater amounts of concrete and steel. In short, precast concrete systems offered a great potential in waste reduction and also a better quality control, which justify their use for public buildings construction.